Entrepreneurial Orientation, Market Orientation and Business Performance (Frozen Food Retail Entrepreneurs of XYZ Business) - Annisa Auliya Rohmah; Fauzan Aziz (AFEBI Management and Business Review, 2022)
The lifestyle has changed and affects changes in consumption patterns leading to consuming processed or frozen products (frozen food). However, the change in consumption also causes the high demand for products from Frozen Food retail entrepreneurs among similar businesses. Every frozen food retail entrepreneur of XYZ business has a different way of making strategies for its retail. This research aims to determine and analyze the effect of entrepreneurial and market Orientation on XYZ's business performance in their entrepreneur's frozen food retail. The research method used in this study is a quantitative method with a descriptive type of research. Sampling was done using the saturated sample method of 37 XYZ frozen food retail entrepreneurs as respondents with questionnaire distribution. The data analysis technique used is descriptive analysis and multiple linear regression analysis. The data processing results using SPSS-25 showed a positive and significant effect of entrepreneurial orientation and market orientation on business performance. Furthermore, entrepreneurial and market orientation affects business performance simultaneously among Frozen food retail entrepreneurs of XYZ business.Keywords: Entrepreneurial Orientation, Market Orientation, Business Performance